China in Africa - Game Changer from the African Perspective? : - David, Mfon-Obong Monday (2019)
The thesis goal is to analysis the nature of China-Africa relation covering the historical aspect, dimensions of China's interest in the continent, its policy, cooperation mechanism as well as the impacts of their relation within the political and economic dimensions.